2023
DOI: 10.26786/1920-7603(2023)711
|View full text |Cite
|
Sign up to set email alerts
|

Fishing for flies: testing the efficacy of “stink stations” for promoting blow flies as pollinators in mango orchards

Abstract: Pollinator communities are composed of diverse groups of insects, with radically different life histories and resource needs. Blow flies are known to visit a variety of economically important crop plants. Larval blow flies develop by feeding on decaying animals. Some fruit growers are known to place carrion on farms during the flowering season to attract adult blow flies (Calliphoridae). However, the efficacy of these “stink stations” has not been tested. We conducted a series of experiments to determine: 1) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 109 publications
1
5
0
Order By: Relevance
“…Further, A. mellifera bees were typically seen in high numbers visiting umbels within fields but were more abundant visitors of male fertile umbels compared to male sterile umbels. This finding concurs with other studies that suggest that A. mellifera honey bees are generally inefficient pollinators of hybrid carrots as: (1) honey bees find hybrid male fertile carrot flowers unattractive and thus visit them less frequently than hybrid male sterile flowers (Broussard et al, 2017;Delaplane & Mayer, 2000;Gracie, 2011;Mas et al, 2018), and (2) honey bees rarely move pollen between hybrid parent lines, choosing to instead forage along parent lines (Erickson et al, 1979;Gaffney, 2011;Gaffney et al, 2011Gaffney et al, , 2019Spurr, 2003) (Finch et al, 2023;Pain, 2021), and has been demonstrated…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Further, A. mellifera bees were typically seen in high numbers visiting umbels within fields but were more abundant visitors of male fertile umbels compared to male sterile umbels. This finding concurs with other studies that suggest that A. mellifera honey bees are generally inefficient pollinators of hybrid carrots as: (1) honey bees find hybrid male fertile carrot flowers unattractive and thus visit them less frequently than hybrid male sterile flowers (Broussard et al, 2017;Delaplane & Mayer, 2000;Gracie, 2011;Mas et al, 2018), and (2) honey bees rarely move pollen between hybrid parent lines, choosing to instead forage along parent lines (Erickson et al, 1979;Gaffney, 2011;Gaffney et al, 2011Gaffney et al, , 2019Spurr, 2003) (Finch et al, 2023;Pain, 2021), and has been demonstrated…”
Section: Discussionsupporting
confidence: 90%
“…The habitat in which we observed E. punctulatus fly oviposition can likely be recreated in other crop agroecosystems to support and encourage beneficial eristaline syrphid fly development. Deployment of resources, such as placing manure or carrion near flowering plants to attract pollinators, is common in Australian mango cropping systems (Finch et al., 2023; Pain, 2021), and has been demonstrated to benefit urban environments (Cusser et al., 2021). To support E. punctulatus oviposition, we recommend placing discarded plant material near fields before, or in between, periods of crop bloom to create a habitat for the immature stages of E. punctulatus to develop.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The abundance and diversity of insects that provide pollination services within agroecosystems often depend on suitable habitat options for the insects to complete their life cycles [ 1 , 2 ]. These habitats (e.g., remnant vegetation, semi-natural landscape features) are typically not within the crop system itself, but nearby, and provide food, reproduction sites, overwintering resources, and shelter from agricultural management practices such as tilling, harvesting, and pesticide application [ 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%